Comic Sounds in Contemporary Theatre Performances: Marthaler, Pollesch, Fritsch and Gotscheff - Rost, Katharina (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2015)
At the Volksbühne am Rosa-Luxemburg-Platz in central Berlin, directors René Pollesch, Christoph Marthaler, Herbert Fritsch, and Dimiter Gotscheff employ comical elements of slapstick, irony, black humour, exaggeration, bluntness, vulgarity, and absurdity. Sound often proves to be significant to the comical effect of the performances as the use of music, sound effects and a specific way of speaking are characteristic for each of their individual directing styles. Even though their styles are comparable in that they all use of a vast array of acoustic elements, they nevertheless differ greatly from each other. The aim of my article is to categorize their use of comical sounds by considering how and to what effect they are employed. The comical aspect of sounds, situations or actions is not necessarily universal or trans-historical, but rather always depends on the specific cultural and historical context that also coins the specific contemporary theatre practice. The article focusses on these connections and on the shifts of attention that are mainly caused by the comical effects of sound and can cause further comical effects.